2019
DOI: 10.5755/j01.ee.30.5.22820
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Consumer Value of Omni-Channel Service Attributes in Japan and Korea

Abstract: Digitization of retail platform and integration of various retail channel is coupled with rapid change in consumer shopping behavior and their expectation for retail experience. Consumers expect retailers to be able to provide seamless, consistent and personalized service in which they also have enriched retail experience (Picot Coupey et al., 2016). Omni-channel retailing has emerged to provide integrated retail service of various channels which enable consumers to use various channels and touch points synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…However, our results revealed a strong influence of shopping value, measured as brand equity, on loyalty. We, therefore, agree with [52] when proposing that retailers invest in building brand loyalty in the online environment, and with [4] when they state that if the retailer's brand is recognized by consumers and translates into true brand loyalty, consumers will even be willing to switch brands to shop at their favourite store. Retailers must, therefore, conduct in-depth analyses on how to give value to their own brand and use all the tools at their disposal to communicate that value to consumers.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, our results revealed a strong influence of shopping value, measured as brand equity, on loyalty. We, therefore, agree with [52] when proposing that retailers invest in building brand loyalty in the online environment, and with [4] when they state that if the retailer's brand is recognized by consumers and translates into true brand loyalty, consumers will even be willing to switch brands to shop at their favourite store. Retailers must, therefore, conduct in-depth analyses on how to give value to their own brand and use all the tools at their disposal to communicate that value to consumers.…”
Section: Discussionmentioning
confidence: 76%
“…In [51], consumer satisfaction is defined as a customer assessment in terms of whether a service meets their needs and expectations. In an online context, according to [52], consumers perceive that they have an experience with a brand rather than with a channel, and that brand acquires greater importance because it is at the intersection between touchpoints [9]. The authors of [53] demonstrated that brand experience is strongly linked to satisfaction, trust and intentions for future purchasing.…”
Section: Hypothesis and Model Developmentmentioning
confidence: 99%
“…The conclusion about the importance of electronic retailing in contemporary marketing channels can be drawn based on the results of previous research (Hu & Oliveri, 2020;Borkar, 2020;Kordrostami & Rahmani, 2020;Zarie et al, 2020;Wu et al, 2020;Kim et al, 2019;Altıntas et al, 2019), as well as potentials of its growth and relevance of the research problem. Electronic retailing is a consequence of the development of traditional retailing and the application of technology in the business of the largest and strongest retailers in the market, but also itself is a factor drawing the further development of traditional retail (Tunsakul, 2020;Huggins et al, 2020;Altıntas et al, 2019Siqueira et al, 2019.…”
Section: Theoretical Background and Development Of Hypothesesmentioning
confidence: 99%
“…However, no other innovation has received as much attention from retailers, manufacturers, consumers, and the general public as did Internet retailing, or e-tailing; no other form of intertype competition has threatened to upset traditional retailing more than Internet retailing in the last few decades including discount stores, superstores, warehouse stores, direct sales, and home shopping cable networks, where the difference between these retail formats and e-tailing is technology (Rajesh & Prasad, 2020;Wisker, 2020;Pandey, 2019). All the largest retailers, manufacturers, and other participants in the world apply electronic retailing in their business as a factor for achieving market competitiveness (Kim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of studies analyze the use of value in different services, such as tourism and hospitality (Gallarza, Arteaga, & Gil-Saura, 2019), telecommunications (Izogo, 2017), retail (Kim, Matsui, Park, & Okutani, 2019), and financial services (Dootson, Beatson, & Drennan, 2016). However, competitive pressures have grown in other service sectors, too, such as health care (Lakdawalla et al, 2018), public services (Osborne, 2018), and education (Botti, Grimaldi, Tommasetti, Troisi, & Vesci, 2017).…”
Section: Customer Experiences In An Online University Contextmentioning
confidence: 99%